High-performance graphite-phase carbon nitride photocatalyst as well as preparation method and application thereof
By thermal decondensation and polycondensation under water-assisted conditions, a high-performance graphite phase carbon nitride photocatalyst was prepared, which solved the problem of low photocatalytic quantum efficiency of graphite phase carbon nitride materials, achieved significant improvement in photocatalytic performance, and was suitable for Energy and ambient photocatalytics fields.
Patent Information
- Application Number
- CN202411601203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
AI Technical Summary
The photocatalytic quantum efficiency of graphite phase carbon nitride materials is low, which limits its practical application in the fields of energy and ambient photocatalytics.
By using nitrogen-rich organic matter as the precursor and thermally depolymerized under water-assisted conditions, a high-performance graphite phase carbon nitride photocatalyst was prepared. The method includes controlling the temperature at 450-600°C under air atmosphere and normal pressure, and the insulation time is 2-12 hours, and obtaining a high-performance graphite phase carbon nitride photocatalyst after cooling to room temperature.
The photocatalytic performance of graphite-phase carbon nitride materials has been significantly improved, the hydrogen production efficiency has been improved by 5 to 7 times, and the pollutant degradation efficiency has also been significantly improved, and it is suitable for large-scale production.
Smart Images

Figure CN119406443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic material preparation, and in particular relates to a high-performance graphite phase carbon nitride photocatalyst and a preparation method and application thereof. Background Art
[0002] Graphitic carbon nitride is a new type of photocatalytic material with broad application prospects in photocatalytic water splitting to produce hydrogen and degrading organic pollutants. On the one hand, graphitic carbon nitride has excellent thermal and chemical stability, reasonable band gap and band edge structure; on the other hand, the material does not contain metal elements, the preparation method is simple and the raw material price is low. Therefore, graphitic carbon nitride materials have attracted much attention in the field of photocatalytic applications.
[0003] Compared with traditional metal oxide photocatalytic materials, graphite carbon nitride has the characteristics of polymer semiconductors. The system has high exciton binding energy, serious recombination of photogenerated electron-hole pairs, small specific surface area, poor dispersibility of sample powder in solution, and cannot fully utilize sunlight due to its relatively large band gap. Under the combined effect of these factors, the photocatalytic quantum efficiency of graphite carbon nitride materials is still low, which seriously restricts its large-scale practical application in the field of energy and environmental photocatalysis.
[0004] How to further improve the photocatalytic performance of graphite phase carbon nitride materials is a key issue facing this field. Summary of the invention
[0005] The present invention provides a high-performance graphite phase carbon nitride photocatalyst and its preparation method and application. The preparation method has a simple process, does not require complicated post-processing and composite with other material systems, and the photocatalytic performance of the prepared graphite phase carbon nitride material is significantly improved.
[0006] The technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a method for preparing a high-performance graphite-phase carbon nitride photocatalyst, which comprises: using nitrogen-rich organic matter as a precursor, performing thermal decomposition and polycondensation under water-assisted conditions, air atmosphere and normal pressure, the temperature is 450-600°C, the insulation time is 2-12 hours, and the high-performance graphite-phase carbon nitride photocatalyst is obtained after cooling to room temperature.
[0008] Furthermore, the nitrogen-rich organic matter includes any one of melamine, cyanamide, dicyandiamide and urea.
[0009] Furthermore, the water-assisted condition is specifically to continuously introduce water mist during the thermal decomposition and polycondensation process, and the introduction rate of the water mist is 5-20 mL / h.
[0010] Furthermore, the heating rate of the thermal decomposition and polycondensation is 2-15°C / min.
[0011] Furthermore, the method specifically includes: using nitrogen-rich organic matter as a precursor, loading the nitrogen-rich organic matter into a heat-resistant carrier and placing it in the center of a heating furnace; continuously introducing water mist into the heating furnace using an atomizing device, thermally decomposing and polycondensing the nitrogen-rich organic matter in an air atmosphere and under normal pressure, at a temperature of 450 to 600°C and a heat preservation time of 2 to 12 hours; and cooling to room temperature to obtain the high-performance graphite phase carbon nitride photocatalyst.
[0012] Furthermore, the heating furnace is a tubular furnace.
[0013] Furthermore, the heat-resistant carrier includes any one of a quartz boat, a quartz crucible, a ceramic boat and a ceramic crucible.
[0014] The second aspect of the present invention provides a high-performance graphite-phase carbon nitride photocatalyst prepared by the above-mentioned method for preparing a high-performance graphite-phase carbon nitride photocatalyst.
[0015] Furthermore, the high-performance graphite phase carbon nitride photocatalyst has a hydrogen production efficiency of 1713.3 μmol h under light with a wavelength greater than 420 nanometers. -1 g -1 , the pollutant degradation efficiency k is 0.1477min -1 .
[0016] The third aspect of the present invention provides the use of the high-performance graphite-phase carbon nitride photocatalyst as described above in the field of photocatalytic decomposition of water to produce hydrogen and degradation of organic pollutants.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects:
[0018] The present invention provides a high-performance graphite phase carbon nitride photocatalyst and its preparation method and application. First, the preparation method has a simple process flow and is easy to operate. The nitrogen-rich organic matter is pyrolyzed and polymerized under water-assisted conditions, and then polymerized in one step in a normal pressure air atmosphere to prepare a high-performance graphite phase carbon nitride photocatalytic material. This one-step preparation method not only saves costs, but also provides a reference for researchers in the preparation of similar nanomaterials; secondly, the graphite phase carbon nitride material prepared by the present invention has a more uniform degree of polymerization distribution, and the product is mainly in the form of nanosheets, with a larger specific surface area, thereby exposing more edges and active sites, and the photocatalytic performance is greatly improved. In addition, the raw materials used in the present invention are widely available, low in cost, simple in preparation process, and do not require the introduction of any foreign gas, so it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1X-ray diffraction patterns of graphite-phase carbon nitride materials prepared in Example 1 and Comparative Examples 1-2 of the present invention;
[0020] Figure 2 The transmission electron microscope image and selected area electron diffraction image of the graphite phase carbon nitride material prepared in Example 1 of the present invention;
[0021] Figure 3 The nitrogen adsorption-desorption curves of the graphite-phase carbon nitride materials prepared in Example 1 of the present invention and Comparative Examples 1-2 are shown;
[0022] Figure 4 The performance diagram of photocatalytic decomposition of water to produce hydrogen by the graphite phase carbon nitride materials prepared in Example 1 of the present invention and Comparative Examples 1-2;
[0023] Figure 5 The photocatalytic pollutant degradation performance diagram of the graphite phase carbon nitride material prepared in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0024] The inventors have found that the methods commonly used at home and abroad can be briefly summarized into the following three categories: 1) increasing the specific surface area by controlling the morphology of the product, such as preparing various nano or porous structures; 2) reducing the band gap by chemical modification or adjusting the product structure to increase its absorption and utilization rate of visible light; 3) compounding with other different types of materials to improve the separation efficiency of photogenerated carriers through band engineering. These methods have made corresponding progress and improved the photocatalytic efficiency of graphite phase carbon nitride materials to a certain extent.
[0025] Graphite-phase carbon nitride materials are mainly prepared by pyrolysis and polycondensation using nitrogen-rich organic small molecules as raw materials, such as melamine, cyanamide, dicyandiamide, urea, etc. Existing research results show that its main physical and chemical properties such as structure, composition, bond valence characteristics are significantly affected by parameters such as raw materials, reaction atmosphere, external reaction environment, pyrolysis temperature, etc. in the preparation process; this also makes the photocatalytic performance of graphite-phase carbon nitride very sensitive to preparation conditions. Therefore, exploring and developing new preparation methods is an effective way to further improve the photocatalytic performance of graphite-phase carbon nitride materials. In view of this, this application is specially proposed.
[0026] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0027] It will be appreciated that other heating furnaces may be used in place of the tube furnace used in the following examples.
[0028] It is to be understood that other atomizing device reactors capable of generating water mist may be used to replace the atomizing device used in the following embodiments.
[0029] It is to be understood that other loading containers, such as a quartz crucible, a corundum boat, and a crucible, etc., may be used to replace the quartz boat used in the following embodiments.
[0030] Example 1: 10 g of melamine was weighed and loaded into an open quartz boat, and placed in the center of a tube furnace; the quartz tube reactor was 120 cm in length and 5.4 cm in inner diameter; water mist was introduced into the tube furnace through an atomizer; both ends of the tube furnace were opened to maintain normal pressure; the temperature was raised to 550°C in air at a heating rate of 10°C / min, the water mist introduction rate was 10 mL / h, and the temperature was kept for 4 hours; after the thermal decomposition and polycondensation were completed, the sample was naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, and then the sample powder was obtained after grinding.
[0031] Example 2: 5 g of melamine was weighed and loaded into an open quartz boat, and placed in the center of a tube furnace; the quartz tube reactor was 120 cm in length and 5.4 cm in inner diameter; water mist was introduced into the tube furnace through an atomizer; both ends of the tube furnace were opened to maintain normal pressure; the temperature was raised to 550°C in air at a heating rate of 15°C / min, the water mist introduction rate was 10 mL / h, and the temperature was kept for 2 hours; after the thermal decomposition and polycondensation were completed, the sample was naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, and then the sample powder was obtained after grinding.
[0032] Example 3: Weigh 20g of melamine into an open quartz boat and place it in the center of a tube furnace; the quartz tube reactor has a length of 120cm and an inner diameter of 5.4cm; water mist is introduced into the tube furnace through an atomizer; both ends of the tube furnace are opened to maintain normal pressure; the temperature is raised to 550°C in air at a heating rate of 2°C / min, the water mist introduction rate is 5mL / h, and the temperature is kept for 8 hours; after the thermal decomposition and polycondensation are completed, the sample is naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which is then ground to obtain a sample powder.
[0033] Example 4: 10 g of melamine was weighed and loaded into an open quartz boat, and placed in the center of a tube furnace; the quartz tube reactor was 120 cm in length and 5.4 cm in inner diameter; water mist was introduced into the tube furnace through an atomizer; both ends of the tube furnace were opened to maintain normal pressure; the temperature was raised to 550°C in air at a heating rate of 10°C / min, a water mist introduction rate of 15 mL / h, and the temperature was kept for 4 hours; after the thermal decomposition and polycondensation were completed, the sample was naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which was then ground to obtain a sample powder.
[0034] Example 5: 10 g of melamine was weighed and loaded into an open quartz boat, and placed in the center of a tube furnace; the quartz tube reactor was 120 cm in length and 5.4 cm in inner diameter; water mist was introduced into the tube furnace through an atomizer; both ends of the tube furnace were opened to maintain normal pressure; the temperature was raised to 450°C in air at a heating rate of 10°C / min, a water mist introduction rate of 20 mL / h, and the temperature was kept for 4 hours; after the thermal decomposition and polycondensation were completed, the sample was naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which was then ground to obtain a sample powder.
[0035] Example 6: Weigh 20g of cyanamide into an open quartz boat and place it in the center of a tube furnace; the quartz tube reactor has a length of 120cm and an inner diameter of 5.4cm; water mist is introduced into the tube furnace through an atomizer; both ends of the tube furnace are opened to maintain normal pressure; the temperature is raised to 550°C in air at a heating rate of 10°C / min, the water mist introduction rate is 10mL / h, and the temperature is kept for 4 hours; after the thermal decomposition and polycondensation are completed, the sample is naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which is then ground to obtain a sample powder.
[0036] Example 7: Weigh 10 g of dicyandiamide into an open quartz boat and place it in the center of a tube furnace; the quartz tube reactor has a length of 120 cm and an inner diameter of 5.4 cm; water mist is introduced into the tube furnace through an atomizer; both ends of the tube furnace are opened to maintain normal pressure; the temperature is raised to 550°C in air at a heating rate of 10°C / min, the water mist introduction rate is 5 mL / h, and the temperature is kept for 4 hours; after the thermal decomposition and polycondensation are completed, the sample is naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which is then ground to obtain a sample powder.
[0037] Example 8: Weigh 30g of urea into an open quartz boat and place it in the center of a tube furnace; the quartz tube reactor has a length of 120cm and an inner diameter of 5.4cm; water mist is introduced into the tube furnace through an atomizer; both ends of the tube furnace are opened to maintain normal pressure; the temperature is raised to 550°C in air at a heating rate of 10°C / min, the water mist introduction rate is 5mL / h, and the temperature is kept for 4 hours; after the thermal decomposition and polycondensation are completed, the sample is naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which is then ground to obtain a sample powder.
[0038] Comparative Example 1: 10 g of melamine was weighed and mixed with 20 mL of deionized water and ultrasonically stirred evenly, then loaded into an open quartz boat and placed in the center of a tubular furnace; the quartz tube reactor was 120 cm long and had an inner diameter of 5.4 cm; both ends of the tubular furnace were opened to maintain normal pressure; the temperature was raised to 550°C in air at a heating rate of 10°C / min and kept warm for 4 hours; after the pyrolysis and polycondensation were completed, the mixture was naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which was then ground to obtain a sample powder.
[0039] Comparative Example 2: 10 g of melamine was weighed and loaded into an open quartz boat, and placed in the center of a tube furnace; the temperature was raised to 550°C in an air atmosphere at a heating rate of 10°C / min, and the temperature was kept for 4 hours; after the pyrolysis and polycondensation were completed, the sample was naturally cooled to room temperature to obtain a graphite phase carbon nitride sample, which was then ground to obtain a sample powder.
[0040] The following performance tests were performed on the sample powders obtained in each embodiment and comparative example:
[0041] Figure 1 The X-ray diffraction diagram of the graphite phase carbon nitride material prepared in Example 1 and Comparative Examples 1-2 of the present invention shows that both Example 1 and Comparative Examples 1-2 are carbon nitride. Figure 1 It can be seen that the graphite phase carbon nitride material has the same diffraction peaks at 27.5° and 13.1°, corresponding to the (002) and (210) crystal planes, respectively, showing a typical graphite phase carbon nitride structure; and the diffraction peak intensity corresponding to Example 1 is slightly weakened, indicating that the interlayer stacking is looser and the nanostructure has been initially formed.
[0042] Figure 2 The transmission electron microscope image and selected electron diffraction image of the graphite phase carbon nitride material prepared in Example 1 of the present invention. It can be seen from the bright field image that the surface of the graphite phase carbon nitride material presents a uniform fish scale structure, the surface is clean and tidy, the structure is looser, contains abundant internal pores, has a higher roughness, and therefore has a larger specific surface area.
[0043] Figure 3 The nitrogen adsorption curves of the graphite phase carbon nitride materials prepared in Example 1 of the present invention and Comparative Examples 1 and 2 are shown. The adsorption curves have obvious hysteresis loop characteristics, indicating that the graphite phase carbon nitride material has an obvious porous structure, and compared with Comparative Examples 1 and 2, its specific surface area and pore volume are significantly increased by up to 12 times, and the specific data are shown in Table 1 below.
[0044] Figure 4 The graph is a comparison of the photocatalytic decomposition of water to produce hydrogen activity of the graphite phase carbon nitride materials prepared in Example 1 of the present invention and Comparative Examples 1-2 under the irradiation of a xenon lamp with a wavelength of more than 420nm. It can be seen that compared with the graphite phase carbon nitride materials in Comparative Examples 1-2, the graphite phase carbon nitride material prepared in Example 1 of the present invention can increase the efficiency of photocatalytic decomposition of water to produce hydrogen by 5-7 times.
[0045] The graphite phase carbon nitride powders prepared in Example 1 and Comparative Examples 1-2 were used as catalysts to test the photocatalytic decomposition of water to produce hydrogen. The specific process is as follows:
[0046] 25 mg of catalyst powder sample was weighed respectively and evenly dispersed in 100 mL of deionized water, 10 vol.% of triethanolamine was added as a sacrificial agent, and 3 wt.% of Pt was loaded on the catalyst surface by in-situ photodeposition of chloroplatinic acid; the mixed solution was placed in a sealed glass container, and evacuated to remove the air in the reactor; then a 300 W xenon lamp light source (equipped with a cutoff wavelength greater than 420 nm) was used to irradiate the mixed solution to perform photocatalytic water decomposition and hydrogen production reaction; the rate of photocatalytic water decomposition and hydrogen production was quantitatively analyzed by gas chromatography, and the test results are shown in Table 1 below.
[0047] Figure 5 The graph is a comparison of the performance of the graphite phase carbon nitride materials prepared in Example 1 of the present invention and Comparative Examples 1-2 in photocatalytic degradation of organic pollutants under irradiation of a xenon lamp with a wavelength of more than 420nm. It can be seen that compared with the graphite phase carbon nitride materials in Comparative Examples 1-2, the graphite phase carbon nitride material prepared in Example 1 of the present invention can improve the efficiency of photocatalytic degradation of organic pollutants by 3 to 7 times.
[0048] The graphite phase carbon nitride powders prepared in Example 1 and Comparative Examples 1-2 were used as catalysts, and the organic dye Rhodamine B was used as a model molecule to test the photocatalytic degradation performance of the materials. The process was as follows:
[0049] Weigh 25 mg of catalyst powder sample and disperse it into 50 mL (concentration of 2×10 -5 M) in a RhB solution, stirred continuously for 1 hour in dark conditions to reach adsorption equilibrium; then irradiated with a 300 W xenon lamp light source (equipped with a cutoff wavelength greater than 420 nm) for photocatalytic degradation reaction; the corresponding degradation constants are shown in Table 1 below.
[0050] Table 1 Performance test results of graphite phase carbon nitride photocatalyst
[0051]
[0052] As can be seen from Table 1, through the implementation mode of the present invention, a high-performance graphite phase carbon nitride photocatalyst can be obtained, as shown in Example 1, which has a high specific surface area and void volume, and can provide more reaction active sites for the photocatalytic reaction; the unique thin layer structure makes the catalyst have excellent dispersibility in the water dispersion reaction system, can fully adsorb organic pollutants, and has obvious advantages in photocatalytic decomposition of water to produce hydrogen and photocatalytic degradation of organic pollutants.
[0053] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-performance graphite-phase carbon nitride photocatalyst, characterized in that: The method comprises: using nitrogen-rich organic matter as a precursor, carrying out thermal decomposition and polycondensation under water-assisted conditions, air atmosphere and normal pressure, at a temperature of 450-600°C, keeping the temperature for 2-12 hours, and obtaining the high-performance graphite phase carbon nitride photocatalyst after cooling to room temperature.
2. The method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to claim 1, characterized in that: The nitrogen-rich organic matter includes any one of melamine, cyanamide, dicyandiamide and urea.
3. The method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to claim 1, characterized in that: The water-assisted condition is specifically to continuously introduce water mist during the thermal decomposition and polycondensation process, and the introduction rate of the water mist is 5-20 mL / h.
4. The method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to claim 1, characterized in that: The heating rate of the thermal decomposition and polycondensation is 2-15°C / min.
5. The method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to claim 1, characterized in that: The method specifically includes: using nitrogen-rich organic matter as a precursor, loading the nitrogen-rich organic matter into a heat-resistant carrier and placing it in the center of a heating furnace; continuously introducing water mist into the heating furnace using an atomizing device, thermally decomposing and polycondensing the nitrogen-rich organic matter in an air atmosphere and under normal pressure, at a temperature of 450 to 600°C and a heat preservation time of 2 to 12 hours; and cooling to room temperature to obtain the high-performance graphite phase carbon nitride photocatalyst.
6. The method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to claim 5, characterized in that: The heating furnace is a tubular furnace.
7. The method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to claim 5, characterized in that: The heat-resistant carrier includes any one of a quartz boat, a quartz crucible, a ceramic boat and a ceramic crucible.
8. A high-performance graphite-phase carbon nitride photocatalyst prepared by the method for preparing a high-performance graphite-phase carbon nitride photocatalyst according to any one of claims 1 to 7.
9. The high performance graphite phase carbon nitride photocatalyst according to claim 8, characterized in that: The high-performance graphite-phase carbon nitride photocatalyst has a hydrogen production efficiency of 1713.3 μmol h under light with a wavelength greater than 420 nanometers. -1 g -1 , the pollutant degradation efficiency k is 0.1477min -1 .
10. Use of the high-performance graphite phase carbon nitride photocatalyst as claimed in claim 8 in the field of photocatalytic decomposition of water to produce hydrogen and degradation of organic pollutants.